U.S. Direct Investment in Canada: Consequences for the U.S. Economy - Vernon, Raymond (Journal of Finance, 1973)
Raymond Vernon, U.S. Direct Investment in Canada: Consequences for the U.S. Economy, The Journal of Finance, Vol. 28, No. 2, Papers and Proceedings of the Thirty-First Annual Meeting of the American Finance Association Toronto, Canada, December 28-30, 1972 (May, 1973), pp. 407-417